Alopecia 2018
DOI: 10.5772/intechopen.79807
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomes: An Exciting and Promising Alcoholic Carrier System for Treating Androgenic Alopecia

Abstract: Androgenetic alopecia (male-pattern hair loss) is characterized by the deposition of dihydrotestosterone at the pilosebaceous unit of the scalp. Oral administration of drugs (like finasteride) which can reverse androgenic alopecia causes undesired effects to the body. Targeting these drugs directly to the pilosebaceous unit of the scalp will enhance the pharmacological response at the desired site by reducing undesired systemic side effects. This chapter discusses about ethosomes, a specially tailored ethanoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This method is mainly utilised for developing multilamellar vesicles. 17 They used a rabbit model for the investigation. They concluded that 5-fluorouracil containing ethosomes showed better results than 5-fluorouracil only.…”
Section: ) Rotary Film Evaporation Methodsmentioning
confidence: 99%
“…This method is mainly utilised for developing multilamellar vesicles. 17 They used a rabbit model for the investigation. They concluded that 5-fluorouracil containing ethosomes showed better results than 5-fluorouracil only.…”
Section: ) Rotary Film Evaporation Methodsmentioning
confidence: 99%
“…Phosphatides (2-5%) [23] L-α-Lecithin, Phospholipon, and Phospholipon 90NG [24] Vesicle formation Edge stimulator [25] Oleic acid, cholalic acid sodium salt, Tween 80, Tween 20, desoxycholic acid sodium salt, and Span 80 [12] It gives the vesicle flexibility and improves penetration.…”
Section: Architecture Excipients Functionmentioning
confidence: 99%
“…Phospholipids (2 %-5%) 24 Soya phosphatidyl choline (S-75), Lipoid S100,Phospholipon 90G. 25 Component which forms vesicles.…”
Section: Gras Listed Rolementioning
confidence: 99%
“…Ethanol, Isopropyl Alcohol, Propylene glycol, transcutol. 25 It provides softness to the vesicle membrane Water ( qs 100) Water Used as a vesicle forming agent Epidermis: It is the outer layer of skin and is made up of keratinocytes. 33 It contains two types of epidermal layers i.e.…”
Section: Alcohol (30% -40%) 13mentioning
confidence: 99%